Perancangan Sistem E-Commerce Berbasis OpenCart Sebagai Solusi Pemasaran Untuk Meningkatkan Penjualan UMKM di Kecamatan Siak - Khairunnisa, Khairunnisa; Annas, Firdaus; Uliyanti, Rinci (Yayasan Lembaga Studi Makwa, 2024)
MSMEs in Siak District, especially those engaged in souvenir handicrafts and snacks, face major challenges in marketing their products. Many MSME players still rely on conventional marketing methods such as leaving goods in stores or pre-ordering, with delivery coverage limited to the surrounding area. Lack of employees and time constraints further exacerbate this condition. In addition, marketing only relies on social media such as Facebook, which cannot keep up with current technological developments. This research aims to design an e-commerce-based promotion system using OpenCart CMS, to facilitate the buying and selling process and introduce MSME products widely. The method used is Research And Development (R&D) with the PPE development model, namely Planning, Production, and Evaluation. The results showed that the development of an OpenCart-based e-commerce system can be a practical solution to improve the competitiveness of MSME products in the Siak District area. With this system, the buying and selling transaction process becomes easier and products can be recognized by a wide audience, as well as utilizing technology to accelerate product marketing and distribution.